“They’ve Got...Personality!” Goals, Traits, and Behavior on the U.S. Supreme Court - Matthew E.K. Hall (Washington University Journal of Law & Policy, 2017)
This Article posits the Supreme Court acts not only as a collection of individuals with individual goals, but as a group of people with difference personality traits. Hall uses five traditional predominant personality traits—conscientiousness, extraversion, agreeableness, neuroticism, and intellect—as a rubric for evaluating the individual behavior of the justices. The Article argues identifying the predominant traits will help suggest which goals—duty, social interaction, social harmony, loss aversion, and intellectual stimulation—each justice will prefer. Hall recommends further comprehensive research be done to identify the justices’ personality traits in order to understand their collective goals and decision making.
Keywords: Roberts Court; Supreme Court; Personality; Goals; Traits; Conscientiousness; Extraversion; agreeableness; neuroticism; intellect